Analisis Bibliometrik Penelitian tentang Gangguan Tidur Pada Pasien Stroke - Hety Meiliany; Azizah Khoiriyati (Universitas Malahayati, 2026)
ABSTRACT Sleep disorders are a risk factor for complications frequently experienced by stroke patients. Research on sleep and stroke continues to increase, but few studies have comprehensively mapped scientific developments in this field. This study aims to analyze global research trends, distribution, and themes related to sleep disorders in stroke patients through a bibliometric approach. This research method uses a quantitative bibliometric approach. Data were obtained from the Scopus database with a period of 2010-2025 using the keywords